2009
DOI: 10.1177/0091270009338481
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Pharmacokinetic Interactions Between Transdermal Rotigotine and Oral Levodopa/Carbidopa

Abstract: This open-label phase I trial assessed potential pharmacokinetic interactions between oral levodopa/carbidopa and transdermal rotigotine treatment at steady state. Twenty-four participants with idiopathic restless legs syndrome (12 per group) received levodopa/carbidopa (100 mg/25 mg bid) and rotigotine (initial dose 2 mg/24 h for 3 days, followed by 4 mg/24 h) in a randomized sequence as monotherapy and in combination during hospitalization for 13 days. Primary pharmacokinetic parameters were AUC(ss) and C(ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…No formal sample size calculation was performed for this exploratory study. However, the results of previous investigations indicated that a sample size of 36 complete cases was sufficient to provide valid parameter estimations for the given population. All subjects who received ≥1 dose of study medication were included in the safety analysis.…”
Section: Methodsmentioning
confidence: 98%
“…No formal sample size calculation was performed for this exploratory study. However, the results of previous investigations indicated that a sample size of 36 complete cases was sufficient to provide valid parameter estimations for the given population. All subjects who received ≥1 dose of study medication were included in the safety analysis.…”
Section: Methodsmentioning
confidence: 98%
“…A second pathway is the formation of N‐desalkyl metabolites with subsequent conjugation [4]. There is no pharmacokinetic interaction with levodopa/carbidopa [5] and rotigotine can be co‐administered with the anti‐emetic domperidone without changes in the pharmacokinetics of rotigotine [6]. Randomized, placebo‐controlled studies have demonstrated efficacy in early Parkinson's disease (PD) as monotherapy [7, 8] and in combination with levodopa in advanced patients [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…No effects on the pharmacokinetics of rotigotine were observed when it was coadministered with levodopa and carbidopa [5,21], domperidone [5,22], or omeprazole [5]. No effects on levodopa, carbidopa [5,21] or ethinylestradiol/levonorgestrel [5] pharmacokinetics were observed when they were coadministered with rotigotine.…”
Section: Pharmacokinetic Properties Of Rotigotine Transdermal Patchmentioning
confidence: 99%